Physicians' Acceptance Analysis of Teleconsultation Implementation in the JKN Program at Primary Health Care Facilities: A Technology Acceptance Model Approach - Misnaniarti Misnaniarti; Rizma Adila Syakurah; Tiara Tarasati (Newinera Publisher, 2026)
The development of digital technology drives the transformation of healthcare services, including thru the implementation of teleconsultation in the National Health Insurance Program (JKN). However, the success of implementing this service heavily depends on the acceptance of doctors as the primary users. This study aims to analyze doctors' acceptance of teleconsultation at First-Level Health Facilities (FKTP) in Palembang City using the Technology Acceptance Model (TAM) approach. This study uses a qualitative method with a case study design. Data were obtained thru in-depth interviews with eight informants consisting of public health center doctors, private clinic doctors, and management personnel. Data analysis was conducted thematically based on the TAM constructs, namely perceived usefulness, perceived ease of use, attitude toward use, and behavioral intention to use. The research results show that teleconsultation is perceived as beneficial in improving service access, initial communication, and patient monitoring, but it has not yet been able to replace face-to-face services due to limitations in clinical aspects. From the perspective of ease of use, the system is considered quite simple, but there are still technical issues such as non-real-time notifications and limited reporting time. Doctors' attitudes toward teleconsultation tend to be positive, but not strong, while the intention to use it is relatively high but more influenced by external policies. In conclusion, the acceptance of teleconsultation is at a fairly good level but not yet optimal. The optimization of implementation requires improvements in system quality, organizational support, as well as clearer policies and incentives so that the utilization of teleconsultation can run effectively and sustainably.